Kecerdasan Emosi Ditinjau Dari Keikutsertaan Dalam Program Meditasi - Baskara, Adya; Soetjipto, Helly P.; Atamimi, Nuryati (Faculty of Psychology, Universitas Gadjah Mada, 2008)
This Â study Â was Â aimed Â to Â see Â theÂ difference Â between Â emotional Â intelligence Â ofÂ those Â who Â participated Â in Â meditationÂ program and those who did not. The subjects of this study were university students. The subjects were divided into 3 groups:meditators who were currently participating in meditation program for 1â€6 months, meditators who were currently participating in meditation program for more than 6 months, and nonâ€meditators. Each group consisted 30 subjects. Anova analysis resulted a coefficient of F = 34. 703, and p < 0.01. The results indicated that there was a difference in emotional intelligence between the 3 groups. Meditators who participated in meditation for more than 6 months had higher emotional intelligence than those who had only participated for 1â€6 months, and nonâ€meditators. There was no difference in emotional intelligence between those who had only participated for 1â€6 months and nonâ€meditators.